The Role of Schools in Raising Awareness of Traffic Law for Students of SMAN 1 Ambon - Yulivia Dasfamudi; R. Hatala; L. Salamor (CV. Rayyan Dwi Bharata, 2022)
This research was conducted based on the findings of the problems found in the state senior high school 1 Ambon. It is knowm that the student of senior high school 1 Ambon lack awareness of traffic laws such as not using helmet when driving, not having driving documents such as driver’s license dan vehicle registration. this study aims to find out what efforts have been made by schools to increase awareness of traffic laws for students at senior high school 1 Ambon. The research is decripstive qualitative, systematic factual and accurate pictures or panting about facts in the field. data collection techniques in this study were observation,interviews and documentation. the results of this study indicate that schools as formal educational institutions in collaboration with the police have carried out socialization about traffic in schools with the aim of increasing awareness of traffic laws for students of senior high school 1 Ambon